A critical examination of the shelf life of nitrile rubber O-Rings used in aerospace sealing applications. (December 2022) - Porter, Christopher; Zaman, Badruz; Pazur, Richard
Highlights: NBR O-Rings stiffen and lose elongation during shelf life aging. Linear Arrhenius kinetic behavior observed up to 85 °C. Activation energies ranged from 60–63 kJ/mol. Activation energies are lower due to sealed packaging. A 7 year shelf life for NBR O-Rings was proposed. Abstract: The shelf life of MS29513-016 nitrile O-Rings was determined by accelerated heat aging from 40 to 85 °C for varying aging times up to 50 weeks. The microhardness, tensile strength and 50% tensile stress all rise as a function of aging time while the elongation at break decreases. The crosslink density by solvent swell followed the development or loss of network chains during the aging process. In this case, the net increase in crosslink density showed a good correlation with the hardness, tensile strength and tensile stress results. Property loss is attributed to the labile nature of the sulfur cure system, the high double bound content of the nitrile rubber and the high level of ester plasticizer in the compound. Activation energies were lower than expected due to the sealed plastic packaging which impeded oxygen migration. Nevertheless, results clearly show that the O-Rings are out-of-specification beyond 7 years of shelf life due to the loss of elasticity (elongation at break < 200%). The nominal 15 year shelf life for nitrile rubber used in aerospace sealing applications according to SAE AS5316 needs to be reconsidered in light of the results.